How Well is the Demand-Driven, Community Management Model for Rural Water Supply Systems Doing? Evidence from Bolivia, Peru and Ghana - Whittington, D.; Davis, J.; Prokopy, L.; Komives, K.; Thorsten, R.; Lukacs, H.; Bakalian, A.; Wakeman, W. (2012)
This paper reports the main findings of a multi-country research project designed to develop a better understanding of the performance of community-managed rural water supply systems in developing countries. Data were collected from households, village water committees, focus groups of village residents, system operators and key informants in 400 rural communities in Peru, Bolivia and Ghana. Our findings suggest that the demand-driven, community management model, coupled with access to spare parts and some technical expertise, has come a long way toward unraveling the puzzle of how best to design and implement rural water supply programs in developing countries. In all three countries, rural water supply projects were working. Among the households included in our sample in Peru and Bolivia, 95% had operational taps at the time of our field visit. In 90% of the villages in Ghana, all project handpumps were still working. Not only had the rural water systems not broken down, but almost all the households in these communities were obtaining at least some of their water from the systems. However, some households were also still using water from other sources. In Ghana, 38% of households still reported using water from unprotected sources (e.g. springs, river, open wells) for drinking and/or cooking. Another troublesome finding is that rural households in the sample villages are paying very little for the improved water services and, as a result, the finances of many village water committees are in poor shape.